Oxytocin ameliorates cisplatin-induced nephrotoxicity in Wistar rats - Ahmed A. Elberry; Shereen M. Refaie; Mohamed W. Kamel; Tarek M. Ali; Hatem Darwish; Osama M. Ashour (Annals of Saudi Medicine, 2013)
BACKGROUND AND OBJECTIVES: The clinical use of cisplatin (CP) is highly limited because of its renal toxicity and the production of reactive oxygen species (ROS) that intensify the cytotoxic effects. Oxytocin (OT) was previously shown to have antioxidant activity. DESIGN AND SETTING: Experimental study on male Wistar albino rats performed in the Faculty of Pharmacy, King Abdulaziz University, Jeddah, Saudi Arabia. METHODS: Forty-eight male Wistar albino rats were classified into four equal groups: a control group, OT only-treated group which received OT twice (500 μg/kg intraperitoneally (ip) 30 minutes and just before saline administration), a CP-induced nephrotoxicity group that received a single dose of CP (7.5 mg/kg ip) and treated with saline, and CP+OT group treated with the same previous doses. Seventy-two hours after CP administration, the rats were sacrificed and blood was withdrawn for determination of urea, creatinine, albumin and lactate dehydrogenase (LDH). The kidneys were extracted for histopathological examination and determination of the tissue levels of reduced glutathione (GSH), thiobarbituric acid reactive substances (TBARS) and nitric oxide end product nitrite (NO2). Glutathione S-transferase (GST), catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx) and myeloperoxidase (MPO) activities were assessed. RESULTS: CP-induced renal injury was evidenced histopathologically and manifested by a significant increase in serum LDH activity as well as urea and creatinine levels. Moreover, renal injury was associated with decreased renal tissue activities of CAT, SOD, GPx and GST as well as GSH level. On the other hand, renal tissue content of TBARS and NO2 as well as the activity of MPO were increased. Alterations in these biochemical and histopathological indices due to CP were attenuated by OT. CONCLUSION: OT protected rats from CP-induced nephrotoxicity. Such protection is attributed, at least in part, to its antioxidant activity.